Resurgence of lymphogranuloma venereum in Western Europe: an outbreak of Chlamydia trachomatis serovar l2 proctitis in The Netherlands among men who have sex with men - Nieuwenhuis, Rutger F; Ossewaarde, Jacobus M; Götz, Hannelore M; Dees, Jan; Thio, H Bing; Thomeer, Maarten G J; den Hollander, Jan C; Neumann, Martino H A; van der Meijden, Willem I (Clinical infectious diseases, 2004)
Lymphogranuloma venereum (LGV) is a sexually transmitted disease (STD) and is rare in the Western world. Recently, 3 men who have sex with men presented with LGV proctitis at the Erasmus Medical Center, Rotterdam, The Netherlands. We investigated a possible outbreak in a sexual network of men who have sex with men (MSM). After active case finding, a total of 15 men presented and were investigated. Serum antibody titers to Chlamydia trachomatis were determined. Urine and rectum specimens were analyzed by polymerase chain reaction (PCR) for the presence of C. trachomatis. C. trachomatis-positive specimens were genotyped to detect the specific C. trachomatis serovars. All subjects underwent routine STD screening. Sociodemographic, clinical, and endoscopic characteristics were evaluated. Thirteen subjects had high immunoglobulin (Ig) G and IgA titers to C. trachomatis, suggesting an invasive infection. Rectal specimens of 12 subjects were PCR-positive for C. trachomatis. All urine specimens were negative. Genotyping revealed serovars L(2) (n=8) and L(1) (n=1). An ulcerative proctitis was found in all subjects obtaining sigmoidoscopy (n=9). Eleven of 13 subjects with an LGV diagnosis were seropositive for human immunodeficiency virus (HIV), 6 had another concomitant STD, and 1 had recently acquired a hepatitis C virus infection. Further sexual contacts were reported from The Netherlands, Germany, Belgium, the United Kingdom, and France. We revealed an outbreak of LGV proctitis among MSM in The Netherlands. The ulcerous character favors transmission of HIV, other STDs, and blood-borne diseases. From a public health perspective, it seems important to increase the awareness of possible LGV in MSM with symptomatic proctitis.